Clinical Practice Guidelines for Stroke of Chinese Medicine Rehabilitation - Working Group of Clinical Practice Guidelines for Stroke of Chinese Medicine Rehabilitation; Zhicheng LIN; Xiehua XUE; Yijing JIANG; Yongmei YOU; Jun WANG; Zengtu ZHAN; Min XIA; Wei WEI (康复学报)
The characteristic of stroke is high morbidity, high mortality, high disability and high recurrence rate. Based on evidence-based medicine, rehabilitation is the most effective method to reduce the disability rate. At the present stage, TCM rehabilitation has a good medical foundation. Making the guidelines for stroke of Chinese medicine rehabilitation is necessary to standardize the treatment behavior of stroke rehabilitation with TCM, so as to improve the rehabilitation effect. The guidance introduces the diagnosis and treatment process of stroke from scope, terms and definitions, diagnosis, rehabilitation management, rehabilitation assessment, rehabilitation of different dysfunction, TCM syndrome differentiation and treatment. It is suitable for clinical doctors in rehabilitation department of TCM, rehabilitation department of integrated traditional Chinese and Western medicine, acupuncture and moxibustion department and massage department. This guide has good applicability and effectiveness.